Kepemimpinan Dan Kinerja Aparatur Sektor Publik - Arielman Zendrato (CV. SINAR HOWUHOWU, 2026)
This study aims to analyze the influence of leadership style on employee performance in the public sector. Leadership style plays an important role in shaping work behavior, motivation, and job satisfaction which ultimately impacts employee performance. This study uses an associative method, namely research that aims to determine the influence or relationship between two or more variables, where the object of study is “Leadership and Employee Performance”, with a literature review approach (library research) to analyze the influence of leadership style on employee performance in the public sector. The results of the study indicate that transformational and democratic leadership styles have a positive and significant influence on employee performance, while authoritarian leadership styles have a positive but insignificant influence. Supporting factors such as effective communication, participation in decision making, and rewarding have been shown to strengthen the relationship between leadership style and employee performance. These findings indicate the importance of the role of participatory and inspirational leadership in increasing productivity and quality of service in the public sector. Leadership style, employee performance, public sector.